BMY-28100 IN RESPIRATORY INFECTION - MIYAHARA, SATOKO; HAYASHI, TOKIKO; MAEDA, FUMIHIKO; SEKI, MASAHIKO; SENJU, SHOUJI; YOSHIDA, MINORU; TOYOSHIMA, HIDEO; YANO, ATSUSHI; ARITOMI, TAKAMICHI; IKEDA, AKIHITO (CHEMOTHERAPY, 1989)
We studied the clinical efficacy, bacteriological effect and safety of a new antibiotic, BMY-28100, in respiratory infections. The efficacy of BMY-28100 was clinically evaluated in 18 cases of respiratory infection including 12 cases of acute bronchitis, 4 of bacterial pneumonia, and 2 of chronic respiratory failure with acute exacerbation by respiratory infection. The causative organisms were revealed in 14 cases: Haemophilus influenzae in 6, H, influenzae plus Streptococcus pneumaniae in 1, S. pneumoniae in 2, Pseudomonas aeruginosa in 2, Klebsiella pneumaniae in 2 and Xanthomonas maltophilia in 1. The clinical efficacy rate was 70.6% in all patients. As an adverse reaction, slight elevation of GOT and GPT was found in 2 cases.